Application of Planting Media Composition and Liquid Organic Mushroom Fertilizer Concentration Eternal Luck (JAKABA) on the Growth and Yield of Purple Eggplant (Solanum melongena L.) - Rhendy Rifky Setiawan; Didik Utomo Pribadi; Hadi Suhardjono (LPPM UNIVERSITAS ISLAM KUANTAN SINGINGI, 2026)
The quality of the growing medium and nutrient availability influence eggplant growth and production. This studyaimed to determine the effects of different growing media combined with varying concentrations of liquid organicfertilizer on the growth and yield of eggplant (Solanum melongena L.). A completely randomized design (CRD)with two factors was used: planting media (soil; soil and rice husk charcoal 1:1; soil and goat manure 1:1; soil,rice husk charcoal, and goat manure 1:1:1) and Jakaba POC concentration (15, 30, 45, and 60 ml/L). The resultsshowed a significant interaction between the planting media and Jakaba POC on plant height, number of leaves at28–35 days after planting (DAP), and the number of fruits per plant. The best treatment was the combination ofsoil, rice husk charcoal, and goat manure (1:1:1) with 60 ml/L Jakaba POC. The planting medium significantlyaffected plant height and leaf number at 21, 42, and 49 DAP, as well as fruit weight per plant, while Jakaba POCinfluenced leaf number at 21, 42, and 49 DAP and fruit weight per plant. The combination of organic plantingmedia with Jakaba POC enhanced eggplant growth and yield, particularly plant height, leaf number, and fruitnumber. Based on these results, the combination of soil, rice husk charcoal, and goat manure with 60 ml/L JakabaPOC is recommended as an optimal treatment to improve eggplant growth and production by utilizing organicmaterials that enhance soil physical, chemical, and biological properties.